2019
DOI: 10.1007/s40888-019-00170-8
|View full text |Cite
|
Sign up to set email alerts
|

Are export promotion programs effective in promoting the internalization of SMEs?

Abstract: This paper investigates the impact of Export Promotion Programs (EPPs) in Lombardy -one of the richest region in Italy and one of the four Motors of Europe -on the export performance of beneficiary firms. To assess the impact of the EPPs, we applied a fixed-effect differences-indifferences estimator with ex-ante matching. We shed light on why and how EPPs work by exploring in details what dimensions of export performance respond better to these programs, which support services are more related to export succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 50 publications
(84 reference statements)
1
38
0
Order By: Relevance
“…In a series of empirical papers, Volpe Martincus and Carballo (2008, 2010a, 2010b, 2010c and Volpe Martincus et al (2012) consider various dimensions of export performance in multiple Latin-American countries, presenting evidence suggesting that EPPs mainly promote exports along the extensive margin, both in terms of the number of products exported and the number of destination countries and particularly for exports of heterogeneous goods and for smaller firms. The latter finding confirms the hypothesis that smaller firms generally perceive barriers to exporting more strongly than do larger firms, a finding corroborated by Comi and Resmini (2020) using data on EPPs in the Italian region of Lombardy. In addition, their analysis also confirms that EPPs are most effective along the extensive margin.…”
Section: Exporting and Export Promotionsupporting
confidence: 80%
“…In a series of empirical papers, Volpe Martincus and Carballo (2008, 2010a, 2010b, 2010c and Volpe Martincus et al (2012) consider various dimensions of export performance in multiple Latin-American countries, presenting evidence suggesting that EPPs mainly promote exports along the extensive margin, both in terms of the number of products exported and the number of destination countries and particularly for exports of heterogeneous goods and for smaller firms. The latter finding confirms the hypothesis that smaller firms generally perceive barriers to exporting more strongly than do larger firms, a finding corroborated by Comi and Resmini (2020) using data on EPPs in the Italian region of Lombardy. In addition, their analysis also confirms that EPPs are most effective along the extensive margin.…”
Section: Exporting and Export Promotionsupporting
confidence: 80%
“…A study conducted in Italy confirmed that micro and small firms benefit the most from institutional networking, especially with a government export and promotion agency (Comi & Resmini, 2020). Support from governmental institutions makes it possible for SMEs with a lack of resources to access opportunities in the international market.…”
Section: Institutional Networking and Smes' Internationalisationmentioning
confidence: 95%
“…Studies on the impact of an export promotion programme run by a French government institution (Catanzaro & Teyssier, 2020) and an Italian government institution (Comi & Resmini, 2020) reported conclusive results. SMEs that engage with government institutions through an export promotion programme tend to have better export performance than non-assisted SMEs.…”
Section: Institutional Networking and Smes' Internationalisationmentioning
confidence: 99%
“…Four articles 13 find positive effects of grants, subsidies, and vouchers for commercialisation activities on firm performance. Comi and Resmini (2019) are able to estimate the effects of vouchers for promoting the participation of firms in international fairs and exhibitions abroad, for economic missions abroad, and for external counseling, finding positive effects for each of the supported activities. It should be noted that the policy evaluated by Comi and Resmini (2019) is an EPP; however, the stark difference with other EPPs (in item 1 of Table 2) is that the final provider of the Note: The studies are grouped by institutional setting and policy information provided in the articles.…”
Section: Grants Subsidies and Vouchers For Commercialisation Activitiesmentioning
confidence: 99%